Scutellarin mitigates high glucose-induced pyroptosis in diabetic atherosclerosis: Role of Nrf2-FBXL2-mediated NLRP3 degradation - Qingxin Meng; Yongpan Huang; Xian Long; Lijing Liu; Yani Tang; Jingjing He; Yayuan Luo (Endocrine Journal)
This study investigated the role of scutellarin (Scu) and Nrf2 in diabetic atherosclerosis, focusing on their effects on FBXL2 and NLRP3 ubiquitination. Human umbilical vein endothelial cells were treated with high glucose (HG) to model diabetic atherosclerosis in vitro. Cell viability, cytotoxicity, pyroptosis, and inflammatory cytokine levels were assessed, and gene interactions were examined by dual-luciferase reporter assays. Ubiquitination and protein levels were analyzed through immunoprecipitation and western blotting. The results revealed that HG treatment decreased Nrf2 and FBXL2 levels and enhanced NLRP3-mediated pyroptosis. However, Scu treatment increased Nrf2 expression, improved cell viability, and inhibited pyroptosis. Nrf2 knockdown downregulated FBXL2 and reversed the protective effects of Scu. Additionally, FBXL2 promoted the ubiquitination-mediated degradation of NLRP3 and suppressed pyroptosis. The activation of NLRP3 reversed the protective effects of Scu on diabetic atherosclerosis. These findings suggest that Scu alleviated diabetic atherosclerosis by increasing Nrf2 and FBXL2 expression, promoting NLRP3 ubiquitination-mediated degradation, and suppressing pyroptosis.